FLAMENCO CULTURE: A REFLECTION OF MARGINALIZED COMMUNITIES OR A CELEBRATION OF RESISTANCE? - Antonio, José Martinez Gomez; Lopez Ramirez, Elena Sofia (International Journal of Allied Research in Sociology and Anthropology, 2023)
This multidisciplinary work explores the phenomenon of cultural appropriation, drawing inspiration from the field of Social Anthropology and its methodologies and tools. Cultural appropriation, a concept of growing significance in the contemporary era, refers to the process by which individuals or communities adopt patterns and preferences from their original culture or a specific subset thereof. The incessant usage of this concept underscores its relevance in understanding the dynamics of culture and identity in a globalized world. This study contemplates the implications of cultural appropriation within the context of global cultural pressures and the influence of more dominant cultures. It raises questions about whether cultural appropriation would be a necessary process in the absence of such external influences. In this hypothetical scenario, individuals and communities could naturally develop their own unique cultures, akin to an amniotic fluid nourishing and protecting their cultural identity from extraneous influences